A Novel Intrauterine Device for the Spatio-Temporal Release of Norethindrone Acetate as a Counter-Estrogenic Intervention in the Genitourinary Syndrome of Menopause - Ahmed Abdelgader; Mershen Govender; Pradeep Kumar; Yahya E. Choonara (MDPI AG, 2024)
The genitourinary syndrome of menopause (GSM) is a widely occurring condition affecting millions of women worldwide. The current treatment of GSM involves the use of orally or vaginally administered estrogens, often with the risk of endometrial hyperplasia. The utilization of progestogens offers a means to counteract the effects of estrogen on the endometrial tissue, decreasing unwanted side effects and improving therapeutic outcomes. In this study, a norethindrone acetate (NETA)-loaded, hollow, cylindrical, and sustained release platform has been designed, fabricated, and optimized for implantation in the uterine cavity as a counter-estrogenic intervention in the treatment of GSM. The developed system, which comprises ethyl cellulose (EC) and polycaprolactone (PCL), has been statistically optimized using a two-factor, two-level factorial design, with the mechanical properties, degradation, swelling, and in vitro drug release of NETA from the device evaluated. The morphological characteristics of the platform were further investigated through scanning electron microscopy in addition to cytocompatibility studies using NIH/3T3 cells. Results from the statistical design highlighted the platform with the highest NETA load and the EC-to-PCL ratio that exhibited favorable release and weight loss profiles. The drug release data for the optimal formulation were best fitted with the Peppas-Sahlin model, implicating both diffusion and polymer relaxation in the release mechanism, with cell viability results noting that the prepared platform demonstrated favorable cytocompatibility. The significant findings of this study firmly establish the developed platform as a promising candidate for the sustained release of NETA within the uterine cavity. This functionality serves as a counter-estrogenic intervention in the treatment of GSM, with the platform holding potential for further advanced biomedical applications.